Investimentos financiados pelo BNDES e o optionapproach: uma análise com dados em painel - Marchezan, Aloisio Angelo (2008)
From the concept of option-approach and its influence on levels of investment in times of economical instability in a nation, an assumption was built, based an empirical study of Alves and Luporini (2007), in which the main variables that capture the Brazilian economical instability also had a negative relationship on the investments made with funds of Brazilian Development Bank (BNDES) for the period of 1995 to 2006. This study aimed to test this assumption. There fore an equation of investment was estimated to business fortunes of the institution's resources, with the method of data analysis in panel. The results validated the assumption in parts, indicating that in times of economical instability, the o raise interest rates raise on short-term (SELIC) and the devaluation of the exchange rate increased business investment with resources from BNDES. Meanwhile, the General Price Index - Internal Availability (IGP-DI) has meant that companies postpone their investment decisions in the institution's resources, are waiting for new and better information.